Map and characteristics of local and hyperlocal digital media in Spain - Negreira-Rey, María-Cruz (2020)
During the last two decades, the traditional media model of the local press has suffered a deep crisis which, together with the economic one, has led to the closure of many newspapers and staff cuts. The growing need for a truthful local news offer and the adverse labor reality in the communication sector have motivated many journalists to found their own local and hyperlocal media in the network. In this research, an exploratory study is carried out to elaborate the first map of local and hyperlocal online media in Spain, with the objective of knowing the presence of this type of media in the State. Subsequently, these online media are subjected to a content analysis to identify their basic characteristics and development trends. The results show a relevant growth of local and hyperlocal online media in the country, and their features reflect the search for new information models from proximity.